2017
DOI: 10.1007/s00426-017-0844-z
|View full text |Cite
|
Sign up to set email alerts
|

Delta plots with negative-going slopes as a potential marker of decreasing response activation in masked semantic priming

Abstract: Delta plots with negative-going slopes (nDPs) reflect the phenomenon that an RT difference between two conditions is greater for relatively fast than for relatively slow responses. This unusual distributional pattern has predominantly been observed in the spatial Simon task, where it has been interpreted as reflecting the selective inhibition of an automatically activated response. The literature suggesting that a similar fading mechanism influences RTs in masked identity priming inspired us to check an analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…Critically, although the present study highlighted this issue by illuminating the effect of time pressure on congruency effects for standard versions of visual Simon and Eriksen flanker tasks, time-varying distractor-based processes seem to influence behavior in many other versions of conflict tasks. For example, primarily decreasing delta plots have also been observed for auditory Simon effects (Xiong & Proctor, 2016) and priming effects (Ellinghaus & Miller, 2018;Schlaghecken et al, 2011), and, conversely, primarily increasing delta plots have also been observed for tactile flanker effects (Baciero et al, 2021), SNARC effects (Moro et al, 2018), and manual Stroop effects (Kinoshita et al, 2017;Pratte et al, 2010). Consistent with the present conclusions, for example, speed instructions reduced the size of manual Stroop effects, and these instructions profoundly affected the decision bounds with narrower bounds under speed than accuracy instructions (Hedge et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Critically, although the present study highlighted this issue by illuminating the effect of time pressure on congruency effects for standard versions of visual Simon and Eriksen flanker tasks, time-varying distractor-based processes seem to influence behavior in many other versions of conflict tasks. For example, primarily decreasing delta plots have also been observed for auditory Simon effects (Xiong & Proctor, 2016) and priming effects (Ellinghaus & Miller, 2018;Schlaghecken et al, 2011), and, conversely, primarily increasing delta plots have also been observed for tactile flanker effects (Baciero et al, 2021), SNARC effects (Moro et al, 2018), and manual Stroop effects (Kinoshita et al, 2017;Pratte et al, 2010). Consistent with the present conclusions, for example, speed instructions reduced the size of manual Stroop effects, and these instructions profoundly affected the decision bounds with narrower bounds under speed than accuracy instructions (Hedge et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…This study presents an exciting modus operandi to answer the issue at hand: what are the neural origins and dynamics of cognitive conflict? A large body of research studying various conflict tasks has characterized fast errors as resulting from early response capture of irrelevant information (Coleman et al, 2017;Dittrich and Stahl, 2017;Duprez et al, 2016;Ellinghaus and Miller, 2017;Houvenaghel et al, 2016;Hughes and Yeung, 2011;Salzer et al, 2014;Stins et al, 2007;Wylie et al, 2009). Using a multivariate analysis techniques capitalizing on trial-to-trial variability in neural signal, we demonstrate that traces of the conflict arise in sensory brain areas that code for relevant and irrelevant Within the framework of the dual-route model, we formulated concrete predictions in a theoretically principled way (de Hollander et al, 2016;Forstmann et al, 2016Forstmann et al, , 2011Turner et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Responses slow down, and errors are more common, when the task-relevant ink colour and task-irrelevant word identity are incompatible. Moreover, as was observed in a large variety of conflict tasks, fast incompatible trials are more prone to errors, as compared to slow or compatible trials (Stroop task: Dittrich and Stahl, 2017;Flanker task: Coleman et al, 2017;Simon task: Wylie et al, 2009; masked priming task: Ellinghaus and Miller, 2017). The underlying process that drives these fast errors is regarded as early response capture by irrelevant information .…”
Section: Introductionmentioning
confidence: 96%
“…If the presence of a co-actor induces participants to code their unique response in terms of left or right relative to the other's response, we expected that the time course of the spatial correspondence effect in the joint Go/NoGo task should follow a similar qualitative pattern to that of the Simon task. To test this result for statistical significance, the slope of the delta plots was estimated for each of the 38 participants separately by linear regressions (Ellinghaus & Miller, 2018).…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%